The Impact of the PI3K/Akt Signaling Pathway in Anxiety and Working Memory in Young and Middle-Aged PDK1 K465E Knock-In Mice - Giménez-Llort, Lydia; Santana-Santana, Mikel; Bayascas, José Ramón (Frontiers in Behavioral Neuroscience, 2020)
Dysfunction and dysregulation at the genetic, neural, and behavioral levels point at the fine-tuning of broadly spread networks as critical for a wide array of behaviors and mental processes through the life span. This brain-based evidence, from basic to behavioral neuroscience levels, is leading to a new conceptualization of mental health and disease. Thus, the Research Domain Criteria considers phenotypic differences observed among disorders as explained by variations in the nature and degree of neural circuitry disruptions, under the modulation of several developmental, compensatory, environmental, and epigenetic factors. In this context, we aimed to describe for the first time the in vivo behavioral impact of tweaking the PI3K/Akt signaling pathway known to play an essential role in the regulation of cellular processes, leading to diverse physiological responses. We explored the effects in young (YA, 3–4 months of age) and mature (MA, 11–14 months of age) male and female PDK1 K465E knock-in mice in a battery of tests under different anxiogenic conditions. The results evidenced that the double mutation of the PDK1 pleckstrin homology (PH) domain resulted in an enhancement of the negative valence system shown as an increase of responses of fear- and anxiety-like behaviors in anxiogenic situations. Interestingly, this seemed to be specific of YA and found regulated at middle age. In contrast, cognitive deficits, as measured in a spatial working memory task, were found in both YA and MA mutants and independently of the level of their anxious-like profiles. These distinct age- and function-dependent impacts would be in agreement with the distinct cortical and limbic deficits in the Akt signaling in the brain we have recently described in these same animals. The elicitation of age- and neuronal-dependent specific patterns suggests that fine-tuning the intensity of the PKB/Akt signal that enables diverse physiological response has also its in vivo translation into the negative valence system and age is a key regulatory factor.